Rapid repairing material for rubber conveying belt and preparation method of rapid repairing material
By using components such as ethylene propylene ternary rubber, hydrogenated styrene-butadiene block copolymer and organic vermiculite in rubber conveyor belt repair materials, a three-dimensional crosslinking network is formed, which solves the problems of insufficient strength and slow curing speed of existing repair materials, and achieves high-strength and rapid repair.
Patent Information
- Application Number
- CN202510622414.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2045-05-15
AI Technical Summary
The strength of the existing rubber conveyor belt repair materials is insufficient, making it difficult to firmly bond with the rubber matrix, and the curing speed is slow, which cannot meet the use requirements under complex working conditions, resulting in easy falling off of the repaired parts and low production efficiency.
Using ethylene propylene ternary rubber as the main matrix, combined with hydrogenated styrene-butadiene block copolymer, organic vermiculite and crosslinking agent, a three-dimensional crosslinking network is formed through esterification reaction, physical entanglement and intercalation composite structure, to improve the mechanical properties and bond strength of the material, and to achieve rapid repair through heating, pressurized molding.
It realizes rapid repair of rubber conveyor belts, with high strength, is not easy to crack, and is firmly bonded, meeting the requirements of use under complex working conditions, shortening the repair time and improving production efficiency.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rubber repair materials, belonging to the patent classification number C08K3 / 00, and specifically relates to a rapid repair material for rubber conveyor belts and a preparation method thereof. Background Art
[0002] Rubber conveyor belts are widely used in industries such as mines, ports, metallurgy, and chemicals, and are key equipment for continuous material transportation. During long-term use, rubber conveyor belts are prone to damage due to reasons such as material impact, wear, scratches, and aging. In order to reduce costs and extend the service life of the conveyor belt, repairing the damaged parts is a common and effective method.
[0003] Currently, there are already various rubber conveyor belt repair materials on the market, such as epoxy resin-based, polyurethane-based, and chloroprene rubber-based materials. These repair materials can, to a certain extent, repair the damaged parts of rubber conveyor belts, but there are still many problems in actual applications. Among them, the most prominent problem is the insufficient strength of the repaired material, which is difficult to meet the usage requirements of the conveyor belt under complex working conditions.
[0004] On the one hand, the bonding strength between the existing repair materials and the rubber conveyor belt matrix is limited. Due to the stable molecular chain structure and low polarity on the rubber surface, it is difficult for the repair materials to form strong chemical bonding or physical entanglement with the rubber matrix. During the operation of the conveyor belt, under the external forces such as material friction and tension stretching, interface separation is likely to occur between the repaired part and the rubber matrix, thereby causing the repair material to fall off. On the other hand, the mechanical properties of most repair materials are difficult to match those of rubber conveyor belts. Rubber conveyor belts need to withstand large tensile stresses, bending stresses, and wear during operation, while the elastic modulus, tensile strength, wear resistance, etc. of the existing repair materials often cannot reach a level similar to that of the original conveyor belt. When the repair material is stressed, due to its inability to effectively disperse and transfer stress, stress concentration is likely to occur inside, resulting in cracks appearing prematurely in the repair area. Once cracks form, during the continuous operation of the conveyor belt, the cracks will rapidly expand, eventually leading to secondary cracking of the repaired part, seriously affecting the normal use and production efficiency of the conveyor belt.
[0005] Secondly, the repair speed of the existing repair materials is slow, and the curing process takes a long time. For example, epoxy resin-based repair materials need to be cured at room temperature for several hours or even dozens of hours. Although the curing time of polyurethane-based materials has been shortened, it still cannot meet the emergency repair requirements. For enterprises with continuous production, a long repair time will cause the production line to stop for a long time, resulting in huge economic losses. Summary of the Invention
[0006] The object of the present invention is to provide a rapid repair material for rubber conveyor belts and its preparation method, so as to solve the technical problems of insufficient mechanical strength and slow curing speed of rubber repair materials proposed in the above-mentioned background technology. The rubber repair material of the present invention can be firmly bonded to the matrix of the rubber conveyor belt, and has excellent mechanical properties itself. After repair, it has high strength and is not prone to secondary cracking, and can rapidly repair the rubber conveyor belt.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A rapid repair material for rubber conveyor belts, comprising the following components by weight:
[0009] 60-70 parts of ethylene propylene diene monomer rubber, 20-30 parts of hydrogenated styrene-butadiene block copolymer, 3-6 parts of trimethylolpropane triacrylate, 4-8 parts of organically modified vermiculite, 2-3 parts of zinc stearate, 5-7 parts of sulfur, 5-8 parts of paraffin oil.
[0010] In the technical solution of the present invention, ethylene propylene diene monomer rubber serves as the main matrix of the rubber repair material to provide excellent mechanical properties and weather resistance. The hydrogenated styrene-butadiene block copolymer is used as a compatibilizer to improve the interfacial compatibility. In addition, the maleic anhydride groups on the hydrogenated styrene-butadiene block copolymer undergo an esterification reaction with trimethylolpropane triacrylate at the vulcanization temperature. At the same time, the styrene block of the hydrogenated styrene-butadiene block copolymer forms an interpenetrating network with the ethylene propylene diene monomer rubber through physical entanglement, enhancing the intermolecular force. Trimethylolpropane triacrylate is used as a crosslinking agent. Under the condition of high-temperature sulfur vulcanization, the acrylate groups react with the rubber molecular chains and the active groups (such as the amino groups modified by silane coupling agent) on the surface of the organically modified vermiculite through a free radical mechanism to construct a three-dimensional crosslinking network, significantly improving the mechanical strength between the rubber and the rubber repair material and the mechanical strength of the repair material itself. The organically modified vermiculite has a layered structure, and the rubber molecular chains can be inserted into the interlayer of the vermiculite to form an "intercalated composite" structure, which is equivalent to the vermiculite playing a physical limiting role on the rubber molecular chains. When the rubber is subjected to external force, this intercalated structure can effectively hinder the relative slippage of the rubber molecular chains, enabling the stress to be more evenly dispersed throughout the rubber matrix, thereby improving the mechanical properties such as the tensile strength and tear strength of the rubber. In addition, vermiculite itself has relatively high hardness and rigidity. After being evenly dispersed in the rubber, it can enhance the overall stiffness of the rubber like rigid particles and improve its ability to resist deformation. Paraffin oil plays a plasticizing role during the processing, promoting the uniform dispersion of each component. At the same time, it partially volatilizes to form a microporous structure in the later stage of vulcanization, which is beneficial for stress buffering. This synergistic effect enables the repair material to form a repair layer combined with the substrate in a short time.
[0011] Preferably, the preparation method of the hydrogenated styrene-butadiene block copolymer comprises the following steps:
[0012] (1) Using cyclohexane as the solvent and n-butyllithium as the initiator, a polymerization reaction is carried out by a three-step anionic polymerization method. First, the first-stage styrene polymerization is initiated, then butadiene is added for the second-stage polymerization, and finally styrene is added to complete the third-stage polymerization to obtain a triblock copolymer;
[0013] (2) The triblock copolymer is hydrogenated using tris(triphenylphosphine)rhodium chloride catalyst to fully hydrogenate the double bonds in the butadiene segment to obtain a hydrogenated polymer;
[0014] (3) The hydrogenated polymer is mixed with maleic anhydride and diisopropylbenzene peroxide initiator, and a melt grafting reaction is carried out in a twin-screw extruder. After the grafting is completed, impurities are removed by Soxhlet extraction with acetone, and finally a hydrogenated styrene-butadiene block copolymer is obtained by vacuum drying.
[0015] Preferably, in the step (3), the addition amount of maleic anhydride is 2-5% of the mass of the hydrogenated polymer.
[0016] Preferably, the addition amount of the diisopropylbenzene peroxide initiator is 0.1-0.3% of the mass of the hydrogenated polymer.
[0017] Preferably, the preparation method of the organic vermiculite includes the following steps:
[0018] (a) The natural vermiculite ore is crushed and sieved to obtain vermiculite powder, and then it is dried to remove the adsorbed moisture to obtain dry vermiculite powder;
[0019] (b) The dry vermiculite powder is mixed with a sodium salt solution, and stirred and reacted at a certain temperature. After the reaction is completed, centrifugal separation is carried out, and it is washed with deionized water until neutral, and finally dried to obtain sodium-based vermiculite;
[0020] (c) The sodium-based vermiculite is mixed with cetyltrimethylammonium bromide, deionized water is added, and an ultrasonic-assisted reaction is carried out at a certain temperature. After the reaction is completed, filtration and washing are carried out to remove the unreacted cetyltrimethylammonium bromide, and finally dried to obtain organically intercalated vermiculite;
[0021] (d) The organically intercalated vermiculite is mixed with 3-aminopropyltriethoxysilane, and ethanol / water solution is added as the solvent, and a reflux reaction is carried out under acidic conditions. After the reaction is completed, centrifugal separation is carried out and washed with ethanol, and finally dried to obtain organic vermiculite.
[0022] In the technical solution of the present invention, as described above, the organic vermiculite has a layered structure, and the rubber molecular chains can be inserted into the interlayer of the vermiculite to form an "intercalation composite" structure. It is equivalent to that the vermiculite plays a physical restriction role on the rubber molecular chains. When the rubber is subjected to an external force, this intercalation structure can effectively hinder the relative slippage of the rubber molecular chains, enabling the stress to be more evenly distributed throughout the rubber matrix, thereby improving the mechanical properties such as the tensile strength and tear strength of the rubber.
[0023] The organic vermiculite prepared in the present invention is different from ordinary vermiculite. Due to the too small interlayer spacing of ordinary vermiculite, the rubber molecular chains cannot be inserted into the interlayer of the vermiculite to form an "intercalation composite" structure. In order to enable the rubber molecular chains to be smoothly inserted into the interlayer of the vermiculite in the present invention, the interlayer spacing of the vermiculite is enlarged and modified. First, the vermiculite is mixed and reacted with a sodium salt solution, and sodium-based vermiculite is obtained through ion exchange to improve its expansibility and dispersibility, which is beneficial to its dispersion in the rubber matrix and conducive to the subsequent intercalation reaction of cetyltrimethylammonium bromide. Then, the sodium-based vermiculite reacts with cetyltrimethylammonium bromide under ultrasonic assistance, enabling the surfactant to be inserted into the interlayer of the vermiculite to increase the interlayer spacing and the compatibility with the rubber, thereby realizing the smooth insertion of the rubber molecular chains into the interlayer of the vermiculite. In addition, in the present invention, the surface of the vermiculite is grafted with a silane coupling agent, which can form a stronger chemical bonding or physical interaction with the rubber molecules, making the interfacial bonding between the vermiculite and the rubber matrix more firm and conducive to improving the mechanical strength of the rubber.
[0024] Preferably, in the step (a), the particle size of the vermiculite powder is controlled to be ≤ 30 μm.
[0025] Preferably, in the step (b), the sodium salt is sodium carbonate.
[0026] Preferably, in the step (c), the mass ratio of the sodium-based vermiculite to the cetyltrimethylammonium bromide is 10:2 - 5.
[0027] In the technical solution of the present invention, cetyltrimethylammonium bromide is used to intercalate sodium-based vermiculite, which increases the layer spacing of vermiculite, facilitates the insertion of rubber molecular chains into the vermiculite interlayer, and improves the mechanical strength of the rubber. To maximize the layer spacing of vermiculite, a sufficient amount of cetyltrimethylammonium bromide must be inserted. Therefore, the present invention controls the mass ratio of sodium-based vermiculite to cetyltrimethylammonium bromide to be less than 10 / 2. However, the research team of the present invention unexpectedly found that as the amount of cetyltrimethylammonium bromide continues to increase, when the mass ratio of sodium-based vermiculite to cetyltrimethylammonium bromide is less than 10 / 5, the curing time of the rubber repair material suddenly increases significantly. Through research, it is found that this is because cetyltrimethylammonium bromide has long-chain alkyl groups and polar quaternary ammonium groups. After excessive addition, the polarity of the reaction system will change significantly. The change in polarity will affect the interaction between vulcanizing agent molecules, disrupt their original orderly arrangement and intermolecular forces, increase the energy required for the vulcanizing agent to crack, thereby slowing down the rate of free radical generation, and thus prolonging the curing time of the rubber.
[0028] Preferably, in the step (d), the mass ratio of the organically intercalated vermiculite to 3-aminopropyltriethoxysilane is 1:0.1-0.3.
[0029] A preparation method of a rubber conveyor belt rapid repair material includes the following steps:
[0030] Preheat the ethylene propylene diene monomer rubber and hydrogenated styrene-butadiene block copolymer, then add them to a mixer for basic mixing, and then add paraffin oil to obtain a mixed material;
[0031] Add a trimethylolpropane triacrylate crosslinking agent and an organic vermiculite reinforcing filler to the mixed material, stir evenly, then add a zinc stearate activator and a sulfur vulcanizing agent, and continue to stir evenly to obtain a mixed material;
[0032] Transfer the mixed material to a mold, perform molding under heating and pressure conditions, and then perform vulcanization treatment to complete the crosslinking reaction to obtain a rubber conveyor belt rapid repair material.
[0033] Compared with the prior art, the beneficial effects of the present invention are:
[0034] 1. The ethylene propylene diene monomer rubber serves as the main matrix to provide good mechanical properties and weather resistance. The hydrogenated styrene-butadiene block copolymer enhances the intermolecular force through esterification reaction and physical entanglement. The trimethylolpropane triacrylate constructs a three-dimensional crosslinking network. The organic vermiculite forms an intercalated composite structure and enhances the stiffness of the material with a rigid reinforcing material. Their combined action significantly improves the mechanical properties such as the tensile and tear strength of the repair material.
[0035] 2. The hydrogenated styrene-butadiene block copolymer acts as a compatibilizer to improve the interfacial compatibility of each component. At the same time, the interface between the organically modified vermiculite and the rubber matrix is firmly bonded, enabling the components of the repair material to act synergistically and ensuring the stability of the overall material performance. Detailed implementation manners
[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0037] The specific specifications of the main raw materials used in the specific embodiments of the present invention are as follows:
[0038] Ethylene propylene diene monomer (EPDM): ENB type, ethylene content 58 - 65%, ENB content 4.5 - 5.5%; Trimethylolpropane triacrylate (TMPTA): purity ≥ 99% (HPLC), acid value ≤ 0.5 mg KOH / g; Zinc stearate: zinc content 10.5 - 11.5%, free acid ≤ 0.5%; Sulfur: purity ≥ 99.5%; Paraffin oil: aromatic content ≤ 3%.
[0039] Example 1
[0040] A rapid repair material for rubber conveyor belts includes the following components by weight:
[0041] 68 parts of ethylene propylene diene monomer, 27 parts of hydrogenated styrene-butadiene block copolymer, 5 parts of trimethylolpropane triacrylate, 7 parts of organically modified vermiculite, 2.5 parts of zinc stearate, 6.5 parts of sulfur, and 7 parts of paraffin oil.
[0042] Preparation of hydrogenated styrene-butadiene block copolymer:
[0043] (1) Prepare a 1000 mL four-necked flask, add 800 mL of cyclohexane as a solvent, and pass nitrogen to exhaust air to maintain an inert environment in the system. Place the flask in a constant temperature water bath and heat it to 50 °C. Weigh 20 g of styrene, slowly add it to the flask, and then add 0.5 g of n-butyllithium initiator, and continuously stir and react for 2 h to complete the first-stage polymerization of styrene. Subsequently, weigh 30 g of butadiene, add it to the flask under nitrogen protection, and continue to react for 3 h for the second-stage polymerization. Finally, add 20 g of styrene and react for 2 h to complete the third-stage polymerization to obtain a triblock copolymer.
[0044] (2) Transfer the above triblock copolymer to a high-pressure reactor, add 0.3 g of tris(triphenylphosphine)rhodium chloride catalyst, introduce hydrogen gas, control the reaction pressure at 5 MPa and the temperature at 80 °C, and react for 6 h to fully hydrogenate the double bonds in the butadiene segment, obtaining a hydrogenated polymer.
[0045] (3) Weigh 100 g of the hydrogenated polymer, place it in a beaker, add 4 g of maleic anhydride and 0.25 g of diisopropylbenzene peroxide initiator, and stir evenly. Transfer the mixture to a twin-screw extruder, set the extruder temperature at 200 °C and the screw speed at 80 r / min, and carry out a melt grafting reaction. After the reaction is completed, extract the product with acetone in a Soxhlet extractor for 12 h to remove impurities, and finally dry it in a vacuum drying oven at 60 °C for 8 h to obtain a hydrogenated styrene-butadiene block copolymer.
[0046] Preparation of organophilic vermiculite:
[0047] (a) Take natural vermiculite ore, crush it with a crusher to a particle size ≤ 30 μm to obtain vermiculite powder. Place the vermiculite powder in a forced-air drying oven and dry it at 105 °C for 6 h to remove adsorbed moisture, obtaining dry vermiculite powder;
[0048] (b) Prepare a 10% sodium carbonate solution, take 100 g of dry vermiculite powder and add it to 800 mL of the sodium carbonate solution, place it in a constant-temperature water bath, and stir and react at 60 °C for 4 h. After the reaction is completed, transfer the mixture to a centrifuge and centrifuge it at a speed of 4000 r / min for 10 min, discard the supernatant, wash the precipitate with deionized water until neutral, and finally dry it at 110 °C for 8 h to obtain sodium-based vermiculite.
[0049] (c) Weigh 50 g of sodium-based vermiculite and 22 g of cetyltrimethylammonium bromide, add them together to 500 mL of deionized water, put them into an ultrasonic reactor, and carry out an ultrasonic-assisted reaction at 50 °C for 3 h. After the reaction is completed, carry out suction filtration, and wash the filter cake with deionized water multiple times until cetyltrimethylammonium bromide is not detected in the washing liquid, and finally dry it at 80 °C for 10 h to obtain organically intercalated vermiculite.
[0050] (d) Weigh 10 g of organically intercalated vermiculite and 2.5 g of 3-aminopropyltriethoxysilane, add them to 300 mL of an ethanol / water solution (volume ratio of ethanol to water is 1:1), add hydrochloric acid dropwise to adjust the pH of the system to 3 - 4, and reflux and react at 80 °C for 6 h. After the reaction is completed, centrifuge the mixture at a speed of 4000 r / min for 10 min, discard the supernatant, wash the precipitate with ethanol 3 times, and finally dry it at 80 °C for 8 h to obtain organophilic vermiculite.
[0051] A preparation method of a rapid repair material for rubber conveyor belts, comprising the following steps:
[0052] Weigh ethylene propylene diene monomer (EPDM) and hydrogenated styrene-butadiene block copolymer, and place them in a forced-air drying oven. Preheat at 60 °C for 2 h. Add the preheated raw materials to a Banbury mixer, set the rotation speed of the Banbury mixer at 60 r / min and the temperature at 80 °C, and conduct basic mixing for 10 min. Subsequently, add paraffin oil and continue mixing for 5 min to obtain a mixed material.
[0053] Add trimethylolpropane triacrylate crosslinking agent and organically modified vermiculite reinforcing filler to the mixed material, and stir for 10 min to make them evenly dispersed. Then add zinc stearate activator and sulfur curing agent, and continue stirring for 10 min to obtain a mixed material.
[0054] Transfer the mixed material to a mold, place it in a flat vulcanizing machine, and carry out compression molding at 160 °C and a pressure of 15 MPa for 10 min. Subsequently, continue vulcanizing at 160 °C for 20 min to complete the crosslinking reaction, and a rapid repair material for rubber conveyor belts is obtained after demolding.
[0055] Example 2
[0056] A rapid repair material for rubber conveyor belts, comprising the following components by weight:
[0057] 62 parts of ethylene propylene diene monomer (EPDM), 23 parts of hydrogenated styrene-butadiene block copolymer, 4 parts of trimethylolpropane triacrylate, 5 parts of organically modified vermiculite, 2.5 parts of zinc stearate, 5.5 parts of sulfur, and 6 parts of paraffin oil.
[0058] Preparation of hydrogenated styrene-butadiene block copolymer:
[0059] (1) Prepare a 1000 mL four-necked flask, add 800 mL of cyclohexane as a solvent thereto, introduce nitrogen to exhaust air, and maintain an inert environment in the system. Place the flask in a constant temperature water bath and heat it up to 50 °C. Weigh 20 g of styrene, slowly add it to the flask, and then add 0.5 g of n-butyllithium initiator, and continuously stir and react for 2 h to complete the first-stage polymerization of styrene. Subsequently, weigh 30 g of butadiene, add it to the flask under nitrogen protection, and continue to react for 3 h for the second-stage polymerization. Finally, add 20 g of styrene as a supplement and react for 2 h to complete the third-stage polymerization to obtain a triblock copolymer.
[0060] (2) Transfer the above triblock copolymer to a high-pressure reactor, add 0.3 g of tris(triphenylphosphine) rhodium chloride catalyst, introduce hydrogen, control the reaction pressure at 5 MPa and the temperature at 80 °C, and react for 6 h to fully hydrogenate the double bonds in the butadiene segment to obtain a hydrogenated polymer.
[0061] (3) Weigh 100 g of the hydrogenated polymer and place it in a beaker. Add 3 g of maleic anhydride and 0.15 g of diisopropylbenzene peroxide initiator, and stir evenly. Transfer the mixture to a twin-screw extruder, set the extruder temperature to 200 °C, and the screw speed to 80 r / min, and carry out the melt grafting reaction. After the reaction is completed, extract the product with acetone in a Soxhlet extractor for 12 h to remove impurities, and finally dry it in a vacuum drying oven at 60 °C for 8 h to obtain the hydrogenated styrene-butadiene block copolymer.
[0062] Preparation of organophilic vermiculite:
[0063] (a) Take the natural vermiculite ore, crush it with a crusher to a particle size ≤ 30 μm to obtain vermiculite powder. Place the vermiculite powder in a forced-air drying oven and dry it at 105 °C for 6 h to remove the adsorbed moisture and obtain the dried vermiculite powder;
[0064] (b) Prepare a 10% sodium carbonate solution. Take 100 g of the dried vermiculite powder and add it to 800 mL of the sodium carbonate solution. Place it in a constant-temperature water bath and stir and react at 60 °C for 4 h. After the reaction is completed, transfer the mixture to a centrifuge and centrifuge it at a speed of 4000 r / min for 10 min. Discard the supernatant, wash the precipitate with deionized water until it is neutral, and finally dry it at 110 °C for 8 h to obtain sodium-based vermiculite.
[0065] (c) Weigh 50 g of sodium-based vermiculite and 15 g of cetyltrimethylammonium bromide, add them together to 500 mL of deionized water, put them into an ultrasonic reaction kettle, and carry out ultrasonic-assisted reaction at 50 °C for 3 h. After the reaction is completed, carry out suction filtration, and wash the filter cake with deionized water multiple times until cetyltrimethylammonium bromide cannot be detected in the washing liquid. Finally, dry it at 80 °C for 10 h to obtain organically intercalated vermiculite.
[0066] (d) Weigh 10 g of organically intercalated vermiculite and 1.5 g of 3-aminopropyltriethoxysilane, add them to 300 mL of an ethanol / water solution (volume ratio of ethanol to water is 1:1), and add hydrochloric acid dropwise to adjust the pH of the system to 3 - 4. Carry out reflux reaction at 80 °C for 6 h. After the reaction is completed, centrifuge the mixture at a speed of 4000 r / min for 10 min, discard the supernatant, wash the precipitate with ethanol 3 times, and finally dry it at 80 °C for 8 h to obtain organophilic vermiculite.
[0067] A preparation method of a rapid repair material for rubber conveyor belts, comprising the following steps:
[0068] Weigh ethylene propylene diene monomer rubber and hydrogenated styrene-butadiene block copolymer, place them in a forced-air drying oven, and preheat at 60 °C for 2 h. Add the preheated raw materials to a mixer, set the mixer speed to 60 r / min and the temperature to 80 °C, and carry out basic mixing for 10 min. Subsequently, add paraffin oil and continue mixing for 5 min to obtain the mixed material.
[0069] Add trimethylolpropane triacrylate crosslinking agent and organophilic vermiculite reinforcing filler to the kneaded material, and stir for 10 min to make it evenly dispersed. Then add zinc stearate activator and sulfur vulcanizing agent, and continue to stir for 10 min to obtain a mixed material.
[0070] Transfer the mixed material to a mold, place it in a flat vulcanizer, and press-mold it at 160 °C and 15 MPa for 10 min. Then continue to vulcanize at 160 °C for 20 min to complete the cross-linking reaction. After demolding, a rapid repair material for rubber conveyor belts is obtained.
[0071] Example 3
[0072] A rapid repair material for rubber conveyor belts, comprising the following components by weight:
[0073] 65 parts of ethylene-propylene-diene monomer rubber, 25 parts of hydrogenated styrene-butadiene block copolymer, 4.5 parts of trimethylolpropane triacrylate, 6 parts of organophilic vermiculite, 2.5 parts of zinc stearate, 6 parts of sulfur, and 6 parts of paraffin oil.
[0074] Preparation of hydrogenated styrene-butadiene block copolymer:
[0075] (1) Prepare a 1000 mL four-necked flask, add 800 mL of cyclohexane as a solvent, and pass nitrogen to exhaust air to maintain an inert environment in the system. Place the flask in a constant temperature water bath and heat it to 50 °C. Weigh 20 g of styrene, slowly add it to the flask, and then add 0.5 g of n-butyllithium initiator. Continuously stir and react for 2 h to complete the first-stage polymerization of styrene. Subsequently, weigh 30 g of butadiene, add it to the flask under nitrogen protection, and continue to react for 3 h for the second-stage polymerization. Finally, add 20 g of styrene and react for 2 h to complete the third-stage polymerization to obtain a triblock copolymer.
[0076] (2) Transfer the above triblock copolymer to a high-pressure reactor, add 0.3 g of tris(triphenylphosphine) rhodium chloride catalyst, pass hydrogen, control the reaction pressure to 5 MPa, and the temperature to 80 °C. React for 6 h to fully hydrogenate the double bonds in the butadiene segment to obtain a hydrogenated polymer.
[0077] (3) Weigh 100 g of the hydrogenated polymer, place it in a beaker, add 3.5 g of maleic anhydride and 0.2 g of diisopropylbenzene peroxide initiator, and stir evenly. Transfer the mixture to a twin-screw extruder, set the extruder temperature to 200 °C, and the screw speed to 80 r / min for melt grafting reaction. After the reaction is completed, extract the product with acetone in a Soxhlet extractor for 12 h to remove impurities, and finally dry it in a vacuum drying oven at 60 °C for 8 h to obtain a hydrogenated styrene-butadiene block copolymer.
[0078] Preparation of Organophilic Vermiculite:
[0079] (a) Take natural vermiculite ore and crush it with a crusher to a particle size ≤ 30 μm to obtain vermiculite powder. Place the vermiculite powder in a blast drying oven and dry it at 105 °C for 6 h to remove adsorbed moisture and obtain dried vermiculite powder;
[0080] (b) Prepare a 10% sodium carbonate solution. Take 100 g of dried vermiculite powder and add it to 800 mL of sodium carbonate solution. Place it in a constant temperature water bath and stir and react at 60 °C for 4 h. After the reaction is completed, transfer the mixture to a centrifuge and centrifuge at a speed of 4000 r / min for 10 min. Discard the supernatant, wash the precipitate with deionized water until it is neutral, and finally dry it at 110 °C for 8 h to obtain sodium-based vermiculite.
[0081] (c) Weigh 50 g of sodium-based vermiculite and 20 g of cetyltrimethylammonium bromide, add them together to 500 mL of deionized water, put them into an ultrasonic reaction kettle, and carry out ultrasonic-assisted reaction at 50 °C for 3 h. After the reaction is completed, perform suction filtration and wash the filter cake with deionized water multiple times until cetyltrimethylammonium bromide is not detected in the washing liquid. Finally, dry it at 80 °C for 10 h to obtain organically intercalated vermiculite.
[0082] (d) Weigh 10 g of organically intercalated vermiculite and 2 g of 3-aminopropyltriethoxysilane, add them to 300 mL of ethanol / water solution (volume ratio of ethanol to water is 1:1), and adjust the pH of the system to 3 - 4 by dropping hydrochloric acid. Carry out reflux reaction at 80 °C for 6 h. After the reaction is completed, centrifuge the mixture at a speed of 4000 r / min for 10 min, discard the supernatant, wash the precipitate with ethanol 3 times, and finally dry it at 80 °C for 8 h to obtain organophilic vermiculite.
[0083] A preparation method of a rapid repair material for rubber conveyor belts includes the following steps:
[0084] Weigh ethylene propylene diene monomer rubber and hydrogenated styrene-butadiene block copolymer, place them in a blast drying oven and preheat at 60 °C for 2 h. Add the preheated raw materials to a mixer, set the mixer speed at 60 r / min and the temperature at 80 °C, and carry out basic mixing for 10 min. Subsequently, add paraffin oil and continue mixing for 5 min to obtain a mixed material.
[0085] Add trimethylolpropane triacrylate crosslinking agent and organophilic vermiculite reinforcing filler to the mixed material, and stir for 10 min to make them evenly dispersed. Then add zinc stearate activator and sulfur vulcanizing agent, and continue stirring for 10 min to obtain a mixed material.
[0086] Transfer the mixed materials into a mold, place it in a flat vulcanizing machine, and press-mold at 160 °C and 15 MPa for 10 min. Subsequently, continue vulcanizing at 160 °C for 20 min to complete the cross-linking reaction. After demolding, a rapid repair material for rubber conveyor belts is obtained.
[0087] Example 4
[0088] A rapid repair material for rubber conveyor belts, comprising the following components by weight:
[0089] 70 parts of ethylene-propylene-diene monomer rubber, 30 parts of hydrogenated styrene-butadiene block copolymer, 6 parts of trimethylolpropane triacrylate, 8 parts of organic vermiculite, 3 parts of zinc stearate, 7 parts of sulfur, and 8 parts of paraffin oil.
[0090] Preparation of hydrogenated styrene-butadiene block copolymer:
[0091] (1) Prepare a 1000 mL four-necked flask, add 800 mL of cyclohexane as a solvent, introduce nitrogen to exhaust air, and maintain an inert environment in the system. Place the flask in a constant temperature water bath and heat it to 50 °C. Weigh 20 g of styrene, slowly add it to the flask, and then add 0.5 g of n-butyllithium initiator. Continuously stir and react for 2 h to complete the first-stage polymerization of styrene. Subsequently, weigh 30 g of butadiene, add it to the flask under nitrogen protection, and continue to react for 3 h for the second-stage polymerization. Finally, add 20 g of styrene and react for 2 h to complete the third-stage polymerization to obtain a triblock copolymer.
[0092] (2) Transfer the above triblock copolymer to a high-pressure reactor, add 0.3 g of tris(triphenylphosphine) rhodium chloride catalyst, introduce hydrogen, control the reaction pressure at 5 MPa and the temperature at 80 °C, and react for 6 h to fully hydrogenate the double bonds in the butadiene segment to obtain a hydrogenated polymer.
[0093] (3) Weigh 100 g of the hydrogenated polymer, place it in a beaker, add 5 g of maleic anhydride and 0.3 g of diisopropylbenzene peroxide initiator, and stir evenly. Transfer the mixture to a twin-screw extruder, set the extruder temperature at 200 °C, and the screw speed at 80 r / min for melt grafting reaction. After the reaction is completed, extract the product with acetone in a Soxhlet extractor for 12 h to remove impurities, and finally dry it in a vacuum drying oven at 60 °C for 8 h to obtain a hydrogenated styrene-butadiene block copolymer.
[0094] Preparation of organic vermiculite:
[0095] (a) Take natural vermiculite ore, crush it to a particle size of ≤30 μm using a crusher to obtain vermiculite powder. Place the vermiculite powder in a forced-air drying oven and dry it at 105 °C for 6 h to remove adsorbed moisture to obtain dry vermiculite powder;
[0096] (b) Prepare a 10% sodium carbonate solution. Add 100 g of dry vermiculite powder to 800 mL of the sodium carbonate solution, place it in a constant temperature water bath, and stir and react at 60 °C for 4 h. After the reaction, transfer the mixture to a centrifuge, centrifuge at a speed of 4000 r / min for 10 min, discard the supernatant, wash the precipitate with deionized water until neutral, and finally dry it at 110 °C for 8 h to obtain sodium-based vermiculite.
[0097] (c) Weigh 50 g of sodium-based vermiculite and 25 g of cetyltrimethylammonium bromide, add them together to 500 mL of deionized water, put them into an ultrasonic reaction kettle, and carry out ultrasonic-assisted reaction at 50 °C for 3 h. After the reaction is completed, perform suction filtration, and wash the filter cake with deionized water multiple times until cetyltrimethylammonium bromide cannot be detected in the washing solution. Finally, dry it at 80 °C for 10 h to obtain organically intercalated vermiculite.
[0098] (d) Weigh 10 g of organically intercalated vermiculite and 3 g of 3-aminopropyltriethoxysilane, add them to 300 mL of an ethanol / water solution (volume ratio of ethanol to water is 1:1), dropwise add hydrochloric acid to adjust the pH of the system to 3 - 4, and reflux and react at 80 °C for 6 h. After the reaction, centrifuge the mixture, centrifuge at a speed of 4000 r / min for 10 min, discard the supernatant, wash the precipitate with ethanol 3 times, and finally dry it at 80 °C for 8 h to obtain organic vermiculite.
[0099] A preparation method of a rapid repair material for rubber conveyor belts includes the following steps:
[0100] Weigh ethylene propylene diene monomer rubber and hydrogenated styrene-butadiene block copolymer, place them in a blast drying oven, and preheat at 60 °C for 2 h. Add the preheated raw materials to a mixer, set the mixer speed at 60 r / min and the temperature at 80 °C, and carry out basic mixing for 10 min. Subsequently, add paraffin oil and continue mixing for 5 min to obtain a mixed material.
[0101] Add a crosslinking agent of trimethylolpropane triacrylate and an organic vermiculite reinforcing filler to the mixed material, and stir for 10 min to make them evenly dispersed. Then add a zinc stearate activator and a sulfur vulcanizing agent, and continue stirring for 10 min to obtain a mixed material.
[0102] Transfer the mixed material to a mold, place it in a flat vulcanizer, and carry out molding at 160 °C and a pressure of 15 MPa for 10 min. Subsequently, continue vulcanizing at 160 °C for 20 min to make the crosslinking reaction complete, and after demolding, obtain a rapid repair material for rubber conveyor belts.
[0103] Example 5
[0104] A rapid repair material for rubber conveyor belts includes the following components by weight:
[0105] 60 parts of ethylene propylene diene monomer rubber, 20 parts of hydrogenated styrene-butadiene block copolymer, 3 parts of trimethylolpropane triacrylate, 4 parts of organic vermiculite, 2 parts of zinc stearate, 5 parts of sulfur, 5 parts of paraffin oil.
[0106] Preparation of hydrogenated styrene-butadiene block copolymer:
[0107] (1) Prepare a 1000 mL four-necked flask, add 800 mL of cyclohexane as a solvent, introduce nitrogen to exhaust air, and maintain an inert environment in the system. Place the flask in a constant temperature water bath and heat it to 50 °C. Weigh 20 g of styrene, slowly add it to the flask, and then add 0.5 g of n-butyllithium initiator. Continuously stir and react for 2 h to complete the first-stage polymerization of styrene. Subsequently, weigh 30 g of butadiene, add it to the flask under nitrogen protection, and continue to react for 3 h for the second-stage polymerization. Finally, add 20 g of styrene and react for 2 h to complete the third-stage polymerization to obtain a triblock copolymer.
[0108] (2) Transfer the above triblock copolymer to a high-pressure reactor, add 0.3 g of tris(triphenylphosphine) rhodium chloride catalyst, introduce hydrogen, control the reaction pressure to 5 MPa, the temperature to 80 °C, and react for 6 h to fully hydrogenate the double bonds in the butadiene segment to obtain a hydrogenated polymer.
[0109] (3) Weigh 100 g of the hydrogenated polymer, place it in a beaker, add 2 g of maleic anhydride and 0.1 g of diisopropylbenzene peroxide initiator, and stir evenly. Transfer the mixture to a twin-screw extruder, set the extruder temperature to 200 °C, and the screw speed to 80 r / min for melt grafting reaction. After the reaction is completed, extract the product with acetone in a Soxhlet extractor for 12 h to remove impurities, and finally dry it in a vacuum drying oven at 60 °C for 8 h to obtain a hydrogenated styrene-butadiene block copolymer.
[0110] Preparation of organic vermiculite:
[0111] (a) Take natural vermiculite ore, crush it with a crusher to a particle size ≤ 30 μm to obtain vermiculite powder. Place the vermiculite powder in a forced-air drying oven and dry it at 105 °C for 6 h to remove adsorbed moisture to obtain dry vermiculite powder;
[0112] (b) Prepare a 10% sodium carbonate solution, take 100 g of dry vermiculite powder and add it to 800 mL of sodium carbonate solution. Place it in a constant temperature water bath and stir and react at 60 °C for 4 h. After the reaction is completed, transfer the mixture to a centrifuge and centrifuge it at a speed of 4000 r / min for 10 min. Discard the supernatant, wash the precipitate with deionized water until neutral, and finally dry it at 110 °C for 8 h to obtain sodium-based vermiculite.
[0113] (c) Weigh 50 g of sodium-based vermiculite and 10 g of cetyltrimethylammonium bromide, add them together to 500 mL of deionized water, put them into an ultrasonic reactor, and carry out ultrasonic-assisted reaction at 50 °C for 3 h. After the reaction is completed, carry out suction filtration, and wash the filter cake with deionized water multiple times until cetyltrimethylammonium bromide cannot be detected in the washing liquid. Finally, dry at 80 °C for 10 h to obtain organically intercalated vermiculite.
[0114] (d) Weigh 10 g of organically intercalated vermiculite and 1 g of 3-aminopropyltriethoxysilane, add them to 300 mL of ethanol / water solution (volume ratio of ethanol to water is 1:1), dropwise add hydrochloric acid to adjust the pH of the system to 3 - 4, and reflux and react at 80 °C for 6 h. After the reaction is over, centrifuge the mixture at a speed of 4000 r / min for 10 min, discard the supernatant, wash the precipitate with ethanol 3 times, and finally dry at 80 °C for 8 h to obtain organic vermiculite.
[0115] A preparation method of a rapid repair material for rubber conveyor belts, comprising the following steps:
[0116] Weigh ethylene propylene diene monomer rubber and hydrogenated styrene-butadiene block copolymer, place them in a forced-air drying oven, and preheat at 60 °C for 2 h. Add the preheated raw materials to a Banbury mixer, set the rotation speed of the Banbury mixer at 60 r / min and the temperature at 80 °C, and carry out basic mixing for 10 min. Subsequently, add paraffin oil and continue mixing for 5 min to obtain a mixed material.
[0117] Add trihydroxymethylpropane triacrylate crosslinking agent and organic vermiculite reinforcing filler to the mixed material, and stir for 10 min to make them evenly dispersed. Then add zinc stearate activator and sulfur vulcanizing agent, and continue stirring for 10 min to obtain a mixed material.
[0118] Transfer the mixed material to a mold, put it into a flat vulcanizer, and carry out molding at 160 °C and 15 MPa pressure for 10 min. Subsequently, continue vulcanizing at 160 °C for 20 min to make the crosslinking reaction complete, and obtain a rapid repair material for rubber conveyor belts after demolding.
[0119] Comparative Example 1
[0120] The difference between Comparative Example 1 and Example 1 is that the repair material does not add hydrogenated styrene-butadiene block copolymer, and the remaining steps are the same.
[0121] Comparative Example 2
[0122] The difference between Comparative Example 2 and Example 1 is that the maleic anhydride grafting reaction is not carried out during the preparation process of hydrogenated styrene-butadiene block copolymer, and the remaining steps are the same.
[0123] Comparative Example 3
[0124] The difference between Comparative Example 3 and Example 1 is that the repair material does not add organophilic vermiculite, and the remaining steps are the same.
[0125] Comparative Example 4
[0126] The difference between Comparative Example 4 and Example 1 is that the organophilic vermiculite in the repair material is replaced with ordinary vermiculite, and the remaining steps are the same.
[0127] Comparative Example 5
[0128] The difference between Comparative Example 5 and Example 1 is that during the preparation of organophilic vermiculite, cetyltrimethylammonium bromide is not used for intercalation treatment of vermiculite, and the remaining steps are the same.
[0129] Comparative Example 6
[0130] The difference between Comparative Example 6 and Example 4 is that the mass ratio of sodium-based vermiculite to cetyltrimethylammonium bromide during the preparation of organophilic vermiculite is 10:6, and the remaining steps are the same.
[0131] Comparative Example 7
[0132] The difference between Comparative Example 7 and Example 4 is that the mass ratio of sodium-based vermiculite to cetyltrimethylammonium bromide during the preparation of organophilic vermiculite is 10:7, and the remaining steps are the same.
[0133] Performance Test
[0134] 1. Tensile Strength Test:
[0135] According to the standard of GB / T 528-2009 "Rubber, vulcanized or thermoplastic - Determination of tensile stress - strain properties", the prepared rubber conveyor belt rapid repair material is made into dumbbell-shaped specimens, and 5 specimens are prepared for each group of examples and comparative examples. Using an electronic universal testing machine, set the tensile speed to 500 mm / min, and conduct the test at room temperature (23 ± 2) °C. Record the maximum force value when the specimen breaks, and calculate the tensile strength through the formula. The calculation results are shown in Table 1.
[0136] 2. Tear Strength Test:
[0137] According to GB / T529-2008 "Rubber, vulcanized or thermoplastic - Determination of tear strength (trouser, right-angle and crescent specimens)", right-angle specimens are used, and 5 specimens are prepared for each group. Install the specimens on an electronic universal testing machine, set the tensile speed to 500 mm / min, and conduct the test in an environment of (23 ± 2) °C. Read the maximum force value when the specimen tears, and calculate the tear strength. The calculation results are shown in Table 1.
[0138] 3. Bonding Strength Test:
[0139] Apply the repair material on the rubber conveyor belt substrate and cure it according to the actual repair process. According to GB / T7124-2008 "Determination of Tensile Shear Strength of Adhesives (Rigid Material to Rigid Material)", make tensile shear specimens, 5 in each group. Use an electronic universal testing machine to conduct tensile tests at a speed of 5 mm / min, record the maximum force value when the specimen fails, and calculate the bond strength. The calculation results are shown in Table 1.
[0140] 4. Curing speed test:
[0141] Take an appropriate amount of repair material and place it in a flat vulcanizing machine under the specified temperature (160 °C) and pressure (15 MPa). Take out the specimen every 5 minutes and test its hardness using a Shore hardness tester. When the hardness reaches the specified value (Shore A hardness 70 ± 5), record the time used as the curing time. The test results are shown in Table 1.
[0142] 5. Abrasion resistance test:
[0143] According to GB / T 9867-2008 "Determination of Abrasion Resistance of Vulcanized Rubber or Thermoplastic Rubber (Rotating Cylinder Abrasion Machine Method)", install the specimen on the rotating cylinder abrasion machine, apply a certain load (5 N), set the rotation speed of the abrasion machine to 40 r / min, and the abrasion time to 60 min. After the test, weigh the mass loss of the specimen and calculate the volume abrasion amount through the formula. The calculation results are shown in Table 1.
[0144] Tensile strength (MPa) Tear strength (kN / m) Bonding strength (MPa) Curing time (min) <![CDATA[Volume wear amount (mm 3 )]]> Example 1 19.1 45 3.5 30 101 Example 2 18.3 42 3.2 33 110 Example 3 18.6 44 3.4 31 106 Example 4 19.5 47 3.9 28 96 Example 5 17.4 39 3.0 35 113 Comparative Example 1 12.6 30 2.1 33 156 Comparative Example 2 14.5 35 2.5 32 135 Comparative Example 3 13.8 33 2.2 33 141 Comparative Example 4 11.6 28 1.8 31 162 Comparative Example 5 14.7 36 2.7 32 133 Comparative Example 6 19.6 48 4.0 53 95 Comparative Example 7 19.8 48 4.2 58 95
[0145] Although the present invention has been described in detail with reference to the foregoing embodiments, for those skilled in the art, they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some of the technical features. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A rapid repair material for rubber conveyor belts, characterized in that, Comprising the following components by weight parts: 60 - 70 parts of ethylene - propylene - diene monomer rubber, 20 - 30 parts of hydrogenated styrene - butadiene block copolymer, 3 - 6 parts of trimethylolpropane triacrylate, 4 - 8 parts of organic vermiculite, 2 - 3 parts of zinc stearate, 5 - 7 parts of sulfur, 5 - 8 parts of paraffin oil.
2. The rapid repair material for a rubber conveyor belt according to claim 1, characterized in that, The preparation method of the hydrogenated styrene - butadiene block copolymer comprises the following steps: (1) Using cyclohexane as a solvent and n - butyllithium as an initiator, polymerization reaction is carried out by the three - step method of anionic polymerization. First, the first - stage styrene polymerization is initiated, then butadiene is added for the second - stage polymerization, and finally styrene is supplemented to complete the third - stage polymerization to obtain a triblock copolymer; (2) Using tris(triphenylphosphine) rhodium chloride catalyst to hydrogenate the triblock copolymer to fully hydrogenate the double bonds in the butadiene segment to obtain a hydrogenated polymer; (3) Mixing the hydrogenated polymer with maleic anhydride and dicumyl peroxide initiator, and carrying out melt grafting reaction in a twin - screw extruder. After grafting is completed, impurities are removed by Soxhlet extraction with acetone, and finally vacuum drying is carried out to obtain the hydrogenated styrene - butadiene block copolymer.
3. A rapid repair material for a rubber conveyor belt according to claim 2, characterized in that In the step (3), the addition amount of maleic anhydride is 2 - 5% of the mass of the hydrogenated polymer.
4. The rapid repair material for a rubber conveyor belt according to claim 3, wherein, The addition amount of the dicumyl peroxide initiator is 0.1 - 0.3% of the mass of the hydrogenated polymer.
5. A rapid repair material for a rubber conveyor belt according to claim 1, characterized in that The preparation method of the organic vermiculite comprises the following steps: (a) Crushing and sieving the natural vermiculite ore to obtain vermiculite powder, and then carrying out drying treatment to remove adsorbed moisture to obtain dry vermiculite powder; (b) Mixing the dry vermiculite powder with a sodium salt solution, stirring and reacting at a certain temperature. After the reaction is completed, centrifugal separation is carried out, and it is washed with deionized water until neutral, and finally dried to obtain sodium - based vermiculite; (c) Mixing the sodium - based vermiculite with cetyltrimethylammonium bromide, adding deionized water, and carrying out ultrasonic - assisted reaction at a certain temperature. After the reaction is completed, suction filtration and washing are carried out to remove the unreacted cetyltrimethylammonium bromide, and finally drying is carried out to obtain organically intercalated vermiculite; (d) Mixing the organically intercalated vermiculite with 3 - aminopropyltriethoxysilane, adding an ethanol / water solution as a solvent, and carrying out reflux reaction under acidic conditions. After the reaction is completed, centrifugal separation is carried out and it is washed with ethanol, and finally dried to obtain organic vermiculite.
6. The rapid repair material for a rubber conveyor belt according to claim 5, characterized in that, In the step (a), the particle size of the vermiculite powder is controlled to be ≤30μm.
7. A rapid repair material for a rubber conveyor belt according to claim 5, characterized in that, In the step (b), the sodium salt is sodium carbonate.
8. A rapid repair material for a rubber conveyor belt according to claim 5, characterized in that, In the step (c), the mass ratio of sodium - based vermiculite to cetyltrimethylammonium bromide is 10:2 - 5.
9. A rapid repair material for a rubber conveyor belt according to claim 5, characterized in that In the step (d), the mass ratio of organically intercalated vermiculite to 3 - aminopropyltriethoxysilane is 1:0.1 - 0.
3.
10. A preparation method of a rapid repair material for a rubber conveyor belt, characterized in that, Comprising the following steps: Pre - heating the ethylene - propylene - diene monomer rubber and the hydrogenated styrene - butadiene block copolymer, then adding them into a mixer for basic mixing, and subsequently adding paraffin oil to obtain a mixed material; Adding a trimethylolpropane triacrylate cross - linker and an organic vermiculite reinforcing filler to the mixed material, stirring evenly, then adding a zinc stearate activator and a sulfur vulcanizing agent, and continuing to stir evenly to obtain a mixed material; Transfer the mixed materials into a mold, carry out molding under heating and pressure conditions, and then conduct vulcanization treatment to complete the cross-linking reaction, thereby obtaining a rapid repair material for rubber conveyor belts.
Citation Information
Patent Citations
Conveyor belt repair method
CN110228215A
Rapid repair material for high-polymerization conveying belt
CN116925444A
High-polymerization rapid repair material for conveying belt and preparation process of high-polymerization rapid repair material
CN118834449A
Rubber composite, processing, conveyor belt applying composite, and manufacturing method
WO2018130189A1